Chlorophyll extraction from leaves, needles and microalgae: A kinetic approach - Miazek, Krystian; Ledakowicz, Stanislaw (International Journal of Agricultural and Biological Engineering, 2013)
Currently, there is a strong focus on industrial production of chlorophyll as a natural pigment. Two factors are required in the economically feasible process to make chlorophyll production: material with high pigment content and efficient extraction mechanism. In this work, extraction of chlorophyll from harvested black locust (Robinia pseudoacacia) leaves, Scots pine (Pinus sylvestris) needles, field sow thistle (Sonchus arvensis) leaves, and green microalga (Chlorella sp.) was discussed. The highest pigment content was detected in Chlorella cells (4.46%) followed by black locust leaves (1.63%), sow thistle leaves (1.48%) and pine needles (0.38%). The chlorophyll extraction rate was the highest for black locust leaves (k = 3.59 h-1), sow thistle leaves (k = 2.90 h-1) and Chlorella cells (k = 2.80 h-1) with the use of methanol as a solvent. In investigated materials, needles showed higher resistance for chlorophyll extraction (k = 0.93 h-1) when compared to leaves and microalgae. Values of extraction kinetic constant were much lower for all materials (0.22 – 1.12 h-1) in the case of using ethanol as a solvent. Black locust leaves and Chlorella cells were proved to be the most attractive materials for chlorophyll production.